Rancang Bangun Website Multimedia Dengan Metode Waterfall Dalam Mempromosikan Katering Bu Lela - Dina Anzani; Supiyandi; Solly Aryza (Jurnal Nasional Teknologi Komputer, 2026)
Bu Lela Catering is one of the UMKM that provides catering services for events such as weddings, birthdays, or office meetings. However, Bu Lela Catering currently relies solely on conventional promotional methods, namely word of mouth. Given this situation, there is a need for a promotional medium that can convey information more effectively and efficiently. Through the use of website-based promotional media, it is hoped that Bu Lela Catering will be able to expand its promotional reach and present product information in a structured manner. The designed website will include various important information such as business profiles, menu lists, catering package options. Bu Lela Catering's website system uses WordPress and was developed using the Waterfall method, which includes the stages of analysis, design, implementation, testing, and maintenance. In general, the design and development of Bu Lela Catering's promotional website are excellent in terms of system and make it easier for customers to access information.